Adjunctive beneficial effect of c-di-GMP, a STING agonist, in enhancing protective efficacy of TLR4-adjuvanted tuberculosis subunit vaccine formulations - Kee Woong Kwon; Eunsol Choi; Hagyu Kim; Hyeong Woo Kim; Sangwon Choi; Seunghyun Lee; Sang-Jun Ha; Sung Jae Shin (Journal of Biomedical Science)
Abstract Background Effective subunit vaccine development requires selecting appropriate adjuvant formulations to trigger desired adaptive immune responses. This study explores the immunogenicity and tuberculosis (TB) vaccine potential of antigens (Ags) combined with Toll-like receptor 4 (TLR4) adjuvants and a stimulator of interferon genes (STING) agonist. Methods In this work, we investigated the combination of Ags with TLR4 adjuvants (monophosphoryl lipid A / dimethyldioctadecylammonium bromide; MPL/DDA or glucopyranosyl lipid adjuvant-stable emulsion; GLA-SE) and a STING agonist, c-di-GMP (CDG). Mice were immunized three times by intramuscular injections at 3-week intervals. The effects of integrating Ags in these adjuvant formulations on the immune response were evaluated, focusing on the generation of Th1-biased, polyfunctional Ag-specific CD4+ T cells and their localization in the lung and spleen. To assess protection, immunized mice were aerogenically challenged with either conventional or ultra-low doses of Mycobacterium tuberculosis (Mtb) 4 weeks after the last immunization. Subsequently, bacterial load and pulmonary inflammation were assessed. Results Integrating ESAT6 Ag in TLR4 and CDG adjuvant formulations remarkably boosted Th1-biased, polyfunctional ESAT6-specific CD4+ T cells in the lungs and spleen, providing durable protection against Mtb infection. The inclusion of CDG promoted mucosal localization of ESAT6-specific CD4+ T cells resembling resident memory phenotypes in the lung parenchyma and increased Ag-specific CD4+ T cells in lung vasculature. Immunization with another vaccine Ag candidate, Ag85B, in GLA-SE plus CDG similarly increased Ag85B-specific CD4+ T cells in the spleen and both lung compartments. Following ultra-low dose Mtb challenge, ESAT6 or Ag85B/GLA-SE/CDG immunizations significantly reduced bacterial loads compared to non-, Bacillus Calmette–Guérin (BCG)-, and ESAT6 or Ag85B/GLA-SE-immunized groups. Importantly, the inclusion of CDG decreased killer cell lectin-like receptor subfamily G member 1 (KLRG1) expression among Ag-specific CD4+ T cells in the lung, correlating with enhanced lung-homing evidenced by expanded lung parenchyma Ag-specific CD4+ T cells, including less-differentiated Th1 cells. Conclusions This study highlights that CDG, when used in combination with TLR4 adjuvants, enhances long-term protective immunity, offering a promising strategy for subunit TB vaccine development. Graphical Abstract